(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Diabetes is a well-known cardiovascular risk factor in both T1DM and T2DM. They have a 4-10 higher risk of developing complications from CVD than the non-diabetic population. The importance of intensive glycaemic control to prevent CVD in T1DM was established in both “The Diabetes Control and Complication Trial” (DCCT) and “Epidemiology of Diabetes Intervention and Complications” (EDIC) trials. Despite the epidemiological evidence that poor glycaemic control can lead to higher incidence of cardiovascular events in T2DM, the intervention trials are still inconclusive. In this report we will highlight the pathophysiology of the effect of hyperglycemia on the cardiovascular system, the effect of medications, and the major Randomized Control Trials (RCTs) looking specifically at the cardiovascular outcome of intensive glycaemic control in T2DM. Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 50-56